The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1208/pt020318
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a freeze-dried CMC/PLGA microsphere matrix of rhBMP-2 on bone healing

Abstract: The hypothesis of this research was that implants of poly(lactide-co-glycolide) (PLGA) microspheres loaded with bone morphogenetic protein-2 (rhBMP-2) and distributed in a freeze-dried carboxymethylcellulose (CMC) m atrix would produce more new bone than would matrix implants of non-protein-loaded microspheres or matrix implants of only CMC. To test this hypothesis it was necessary to fashion microsphereloaded CMC implants that were simple to insert, fit precisely into a defect, and would not elicit swelling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 32 publications
0
16
0
1
Order By: Relevance
“…Periodontal regeneration in dogs (Chen et al, 2007b) acid in copolymer polylactic-co-glycolic acid (PLGA), biodegradation is controlled by changing the proportions of each of the two materials, since PLA degrades much more slowly than PGA. Microspheres of PLGA have since then been evaluated in diverse animal models, such as in rat calvarial bone defects (Kenley et al, 1994), rat femurs (Lee et al, 1994) and in calvarial defects in rabbits (Schrier et al, 2001), forming much more bone when BMPs were delivered via the PLGA particles. Interesting work has been developed by Ruhé and colleagues, using microspheres of PLGA in combination with Ca-P cement, as carriers for rhBMP-2 delivery (Ruhe et al, 2005).…”
Section: Dextran-gelatinementioning
confidence: 99%
“…Periodontal regeneration in dogs (Chen et al, 2007b) acid in copolymer polylactic-co-glycolic acid (PLGA), biodegradation is controlled by changing the proportions of each of the two materials, since PLA degrades much more slowly than PGA. Microspheres of PLGA have since then been evaluated in diverse animal models, such as in rat calvarial bone defects (Kenley et al, 1994), rat femurs (Lee et al, 1994) and in calvarial defects in rabbits (Schrier et al, 2001), forming much more bone when BMPs were delivered via the PLGA particles. Interesting work has been developed by Ruhé and colleagues, using microspheres of PLGA in combination with Ca-P cement, as carriers for rhBMP-2 delivery (Ruhe et al, 2005).…”
Section: Dextran-gelatinementioning
confidence: 99%
“…In vitro studies have shown the bioactivity of BMP-2 was maintained during encapsulation into such microparticles (250-430 µm), despite exposure to organic solvents (32). The PLGA particles were effective in stimulating bone formation in several animal models, such as in rat femurs (33), calvarial defects in rabbits (34), and ovine vertebral bodies (35). While some of these studies measured growth factor release, subsequent studies focused on controlling the BMP-2 release from the PLGA particles by embedding them in a calcium phosphate cement (36) or by surface-grafting heparin to the particles for BMP-2 binding (37).…”
Section: Other Particulate Delivery Systems For Bmp-2mentioning
confidence: 99%
“…Estudios han demostrado que la liberación de rhBMP-2 desde una MP de PLGA es afectada directamente por el peso molecular, la relación entre PLA y PGA, la naturaleza del grupo terminal y la cantidad de rhBMP-2 incorporada en la MP (Anderson et al,2012). En el año 2001 se comparó el uso de MP de PLGA con rhBMP-2 en una matriz de carbometil-celulosa y la misma matriz con MP sin rhBMP-2 (Schrier et al, 2001). En este trabajo, se estudió el efecto de ambos tipos de partículas en un modelo de defecto óseo en calota de conejo.…”
Section: Uso De Rhbmp-2 Encapsulado En Mp De Plgaunclassified